ANALISIS EKONOMI SYARIAH KEBUTUHAN POKOK USAHA MIKRO KECIL DAN MENENGAH ( DEPOT ISI ULANG GALON AIR MINUM DI PASAR CIMAYANG, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR ) SELAMA MASA PANDEMI COVID-19 - Tubagus Rifqy Thantawi; abdul kodir; Ilham Wahyudin Setiawan (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The increasing number of Covid-19 cases is weakening the economy. In situations like this, Micro, Small and Medium Enterprises (MSMEs) can become a mainstay in absorbing labor, replacing consumer goods or semi-finished products. An appeal to prevent the chain of transmission of this virus requires people to stay at home. This has an impact on economic instability and one of those affected is MSMEs. Covid-19 has both positive and negative impacts. This paper examines the impact of the Covid-19 pandemic on income levels in MSMEs. The research method used by researchers is descriptive qualitative, and interviews with relevant sources. The researchers proved that the impact of the income level of UMKM Refill Depots in Cimayang Village, Pamijahan District, Bogor, is more positive because more and more people are staying at home so that the demand for drinking water refills increases. Despite the Covid-19 pandemic, this business activity continues to run smoothly and generate significant economic value while still complying with health regulations.